Supply Of Coconut Water As a Nutritional Supplement Corn Cob Media On Growth White Oysters (Pleurotus ostreatus) - Ananto Ananto (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2021)
Provision of coconut water as an additional nutrient for corncob media against the growth of white oyster mushroom (Pleurotus ostreatus) was carried out at the Jaya Mushroom Farmer Group. This study aims to determine the effect of young coconut water as an additional nutrient in corncob media on the yield of white oyster mushroom (Pleurotus ostreatus). This study used a completely randomized design (CRD) consisting of 5 treatment levels and 2 replications in order to obtain 10 experimental units. Each experimental unit consists of 5 baglogs, so that all 50 baglogs. The treatments consisted of A = 20 kg of cobs: control, B = 20 kg of cobs: 7 liters of coconut water, C = 20 kg of cobs: 8 liters of coconut water, D = 20 kg of cobs: 9 liters of coconut water, E = 20 cobs: 10 liter of coconut water. The observations observed were the number of hoods, length of the hood (cm), width of the hood (cm), and wet weight (kg). The results showed that the provision of young coconut water as a nutritional addition to the corncob media on the results of white oyster mushroom (Pleurotus ostreatus) was found in treatment E = 20 kg: 10 liters of coconut water can give the best results on the results of white oyster mushrooms.